Invitation to computer science - Schneider, G. Michael; Gersting, Judith L. (Cengage Learning, 2016)
Offers a contemporary overview of today's computer science. This non-language-specific approach provides a solid foundation using an algorithm-driven approach that's suitable for the reader's first introduction to the field of Computer Science. It also includes a Digital Lab Manual containing 20 laboratory projects that map directly to the book